Montenegro : Financial Sector Assessment Program-Framework for NonPerforming Loans Workout and Insolvency and Creditor Rights-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper examines the current state of nonperforming loans (NPLs) in Montenegro, assesses the regulatory and supervisory framework as well as the insolvency and creditor rights regime, and makes recommendations for strengthening the framework. The paper evaluates the legal, regulatory, and supervisory regimes in four key areas: (1) creditor rights and enforcement systems (for secured and unsecured credit); (2) debt recovery and informal enterprise workout practices; (3) formal insolvency system (liquidation and reorganization proceedings); and (4) effectiveness of the relevant institutional, regulatory, and supervisory frameworks in implementing laws, regulations, and supervisory requirements in this area. The local and regional boom-bust cycle has left a legacy of high NPLs in Montenegro.